ANALYSIS OF MOTHER'S STRESS COPE FACTORS HELPING CHILDREN STUDY AT HOME DURING THE COVID-19 PANDEMIC - Qurratul A’yun; Yulia Paramita Rusady (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2021)
The COVID-19 pandemic has had an impact on the education sector. In order to reduce the spread of Covid-19, the government implemented a social distancing strategy, one of which was by closing schools. The purpose of this study was to analyze maternal stress coping factors in accompanying children to study at home during the pandemic. Based on the research objectives, the research design used in this study is quantitative analytic. The approach used is cross sectional. Respondents are mothers who have school children in grades 1-6 SD. Respondents who filled out the questionnaire were 137 people. Sampling using total sampling. The research site is in the Pamekasan Dam Village. Based on the results of statistical test data analysis using Kendall Tau, it shows a significant level value of 0.000 <0.05 (p-value then Ho is rejected, meaning that there is a significant relationship with the causes of coping with stress when accompanying children to study at home during the covid-19 pandemic). The effect of umbilical cord care on the length of umbilical cord release p-value = 0.028, the effect of umbilical cord humidity on the length of umbilical cord release p-value = 0.043, the effect of environmental sanitation conditions on the length of umbilical cord release p-value = 0.036. Measuring instruments used in this study were questionnaires and checklists. anything to the baby's umbilical cord. It is recommended to obstetric service practitioners in order to provide umbilical cord care services as recommended in Normal Childbirth Care.